Grammatical Errors in Essays Written by Third-Semester Students of the English Department Study Program - Rames Ivak Parela (Edelweiss : Journal Of Innovation In Educational Research, 2024)
This research aims to analyse the grammatical errors made by the students in writing the English essay. The author uses the types of grammar in academic writing proposed by Yakhontova (2003). The research design is descriptive qualitative, and the technique of analysing the data is content analysis. Based on the analysis, there are five grammatical errors made by students. The errors are spelling, noun, subject-verb agreement, punctuation and pronoun. The students made errors in spelling with the total error is 16% and made errors in noun with the total error is 16%. Furthermore, the students made errors in punctuation with the total error is 28 % and made errors in pronoun with the total error is 20 %. The students made errors in pronoun with the total error is 20 %. Punctuation is the most errors made by the students in writing the essay.